Music teacher education in the Baltic countries - Díaz Mohedo, Mª Teresa (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
This article discusses the music teacher education curricula of some major institutions of higher education in the Baltic countries. We discuss both the new structure in cycles implemented in the frame of the European Space of Higher education (Bachelor, Máster’s degree and Doctorate) as well as the analysis of the different programmes and the instructional-based or music-skill-based approach underlying in the organization of this degrees. This analysis denotes to what extent the idiosyncrasy of every country and its teaching institutions determines different profiles of the music teachers.